Faktor-faktor Penentu Tarif Biaya Audit Eksternal (Audit Fee) pada Perusahaan Non-Keuangan - Robertus Nakacama Erik Tat; Dewi Murdiawati (Jurnal Ilmiah Akuntansi, 2020)
The results of previous studies still indicate inconsistencies related to the determinants of the audit fee. The aims of this research is to examine the effect of company political connection, the existence of independent board commissioner, company complexity, public accounting firm size, and company profitability on the audit fee in non-financial companies listed in the Indonesia Stock Exchange on 2016-2018. The sampling technique that used in this research was purposive sampling and produced the number of sample was 130 companies. The data were analyzed by using multiple linear regression analysis. The results show that political connection, company complexity and public accounting firm size positively influence the audit fee. Meanwhile, the existence of independent board commissioner and company profitability do not affect the audit fee.